Smart Maintenance Program for Solar Photovoltaic (PV) with Cooling System - Ladianghibong, Loraine Angel; Llacuna, Bea Joana; Didulo-Baylon, Aivee Ann (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study developed and evaluated a Smart Maintenance Program for Solar Photovoltaic (PV) systems integrating automated cleaning and a temperature-based water-dripping cooling system to improve PV voltage output and operational performance. A quantitative experimental design was employed using two 150 W, 18 V monocrystalline solar PV systems, one equipped with the smart maintenance system and one unaltered. The developed system used Arduino IDE programming, a motorized wiper, temperature sensor, water pump, and associated control components. Voltage output was measured using a multimeter, while the temperature sensor was used to control the cooling mechanism according to the programmed temperature threshold. Data were collected at 10:00 A.M., 12:00 noon, and 2:00 P.M. for 20 days in General Santos City and analyzed using a paired two-tailed t-test at a 95% confidence level. Results showed that the smart PV panel consistently produced higher and more stable voltage outputs than the non-smart panel, with statistically significant differences at all observation periods. The findings indicate that integrating automated cleaning and temperature-based cooling can contribute to improved PV operational performance under actual outdoor conditions. The study concluded that the smart maintenance system provided a more favorable operating condition for the PV panel compared with the unaltered system. Recommendations included longer experimentation, larger PV panels, improved experimental controls, updated software, optimized panel positioning, enhanced cooling components, and more durable system materials. The study supports SDG 7—Affordable and Clean Energy, SDG 9—Industry, Innovation and Infrastructure, and SDG 12—Responsible Consumption and Production. Its sustainability contribution lies in improving renewable-energy utilization, reducing excessive water use through water recirculation, and supporting more effective and durable solar PV operation.